Lethal Autonomous Weapons Systems - Leal, Salvador (Frónesis, 2024)
This paper seeks to reasonably speculate on the possibilities of Artificial Intelligence in decision-making for the use of lethal autonomous weapons systems, trying to maintain a line away from the dystopianism and the Luddism predominant in publications on the subject as well as naïve utopianism. Administrative decision-making by, or with the help of, an algorithm will be analyzed first, and then the theory will be applied to LAWS. It is concluded that lethal autonomous weapons systems have been used for centuries. AI refines these systems to reduce the indiscriminate damage caused by non-intelligent systems.